Socket Sealing Using Free Gingival Grafts: A Randomized Controlled Trial - Ralitsa Yotsova (Dentistry Journal)
Background: Post-extraction ridge resorption is an inevitable phenomenon that cannot be eliminated but is significantly reduced using additional surgical techniques known as socket preservation. They aim to create favorable conditions for implant placement and prosthetic restoration. This study aims to assess the effect of socket sealing (SS) with free gingival grafts on the vertical resorption of socket walls at the premolar and molar regions over 3 months. Methods: This randomized two-arm controlled trial with parallel groups (1:1 allocation) was conducted at the Department of Oral Surgery, Medical University-Varna, Bulgaria, from 27 June 2022 to 20 April 2023. Forty patients aged 30–65 were equally and randomly allocated to the SS or the control groups. Atraumatic tooth extraction was performed. In the control group, the socket was left on secondary wound healing. In the SS group, the socket orifice was “sealed” with an FGG harvested from the hard palate or maxillary tuberosity. Results: Data analysis demonstrated that SS with an FGG is a successful method for reducing the post-extraction resorption of the socket walls. In addition, this study confirms that the thickness of the buccal wall is a significant factor in its vertical resorption. Conclusions: Socket sealing with an FGG is a valuable method that eliminates the need for flap reflection and compensates for the soft tissue deficit when immediate implant placement or bone augmentation is required. Further research is necessary to determine the role of different factors influencing bone resorption and compare the effect of different socket preservation methods.